Usage of Interactive Methods of Teaching within the Context of System Approach - Pisots’ka, Leonida (Pedagogical Discourse, 2013)
Basic notions of the problem are revealed in the article. The question of usage of interactive methods in the educational process of educational establishment through the prism of the system approach has been risen. The factors of realization of the interactive methods in the educational process have been generalized, their prevalence over the traditional ones have been systematized. The article proves that the effectiveness of interactive methods usage in general depends on the teacher. Interactive methods and means have been singled out and enumerated. Besides the demands to the usage of interactive methods by the teacher have been clearly shaped.